What Is, and What Is Not, A Capitalist Empire. Issue 1 (2nd January 2016) - Parisot, James
ABSTRACT: This study argues that a historical materialist theory of what a capitalist empire is has yet to be fully articulated. It proceeds to lay out such a theory. The paper outlines a theory of capitalist empire situated in relation to a historical materialist conceptualization of how capitalism operates. In this I distinguish state and imperialism as aspects of capitalist empires, but empire itself as something related to, but larger than these historical processes. I also locate capitalist empires in relation to the logic of capitalism and its crises tendencies, and the way the logic of capital plays out over uneven development and the exploitation of a variety of labor forms. Additionally, the paper examines the racialized, gendered, and ecological aspects of capitalist empires in an attempt to begin to explain the political economy of capitalist empires as total social wholes.